Transient neonatal diabetes mellitus with macroglossia diagnosed by methylation specific PCR (MS-PCR) - Hye Young Jin; Jin-Ho Choi; Gu-Hwan Kim; Han-Wook Yoo (Korean Pediatric Society, 2010)
Transient neonatal diabetes mellitus (TNDM) has been associated with paternal uniparental isodisomy of chromosome 6, paternally inherited duplication of 6q24, or a methylation defect at a CpG island of the ZAC or HYMAI gene. We experienced a case of TNDM in which the patient presented with hyperglycemia, macroglossia, and intrauterine growth retardation, caused by a paternally derived HYMAI. An 18-day-old female infant was admitted to the hospital because of macroglossia and recurrent hyperglycemia. In addition to the macroglossia, she also presented with large fontanelles, micrognathia, and prominent eyes. Serum glucose levels were 200–300 mg/dL and they improved spontaneously 2 days after admission. To identify the presence of a maternal methylated allele, bisulfite-treated genomic DNA from peripheral blood was prepared and digested with BssHII after polymerase chain reaction (PCR) amplification with methylation-specific HYMAI primers. PCR and restriction fragment length polymorphism analysis showed that the patient had only the paternal origin of the HYMA1 gene. TNDM is associated with a methylation defect in chromosome 6, suggesting that an imprinted gene on chromosome 6 is responsible for this phenotype.